Violence in Peru 2015 - Garmendia Lorena, Fausto (2016)
The most frequent types of violence occurring currently in Peru, including the political, self-inflicted, interpersonal within the family, produced to women, adolescents and older adults are reviewed. A historical reference to Dante Alighieri's Divine Comedy is made as to its contents on violence and its perspectives for today. It highlights emerging forms of economic, criminal, labor and ecological types of violence. A new classification of violence taking into account the new modalities is proposed. The ecological model to explain the roots of violence is discussed and finally actions and practices are suggested for lessening the prevalence of violence in Peru.